Efficacy of docetaxel, cisplatin, and 5-fluorouracil as an induction chemotherapy in oral squamous cell carcinoma in a tertiary hospital in Saudi Arabia - Mohammad Alessa; Abdullah A. Alhifany; Nouf A. Almatrafi; Ahmed S. Bahaj; Haddad H. Alkaf; Jabir Alharbi; Mohammed Y. Almaghrabi; Hemail M. Alsubaie; Hani Elkhatib; Faisal Albadainah; Sherif Abdelmonim (Elsevier, 2024)
Objective: To assess the efficacy and safety of the induction chemotherapy's combination of docetaxel, cisplatin, and 5-fluorouracil (TPF) in Oral Squamous Cell Carcinoma (OSCC) patients and its positive outcomes on tumor size and surgical resection. Method: A retrospective chart review of patient's medical records was conducted from 2018 to 2023. All patients diagnosed with OSCC and who received induction chemotherapy combination of TPF were included in the study. Patients with other conditions that affect chemotherapy tolerability, other primary malignancy, or incomplete medical records were excluded. Descriptive analysis was undertaken to summarize the data pertaining to tumors before and after administration of the TPF chemotherapy. Result: Five patients met the inclusion criteria. All five patients experienced a reduction in tumor size after receiving the TPF induction chemotherapy. Three patients showed a downstaging to [stage 0] after surgical resection. Specifically, one patient demonstrated a reduction in overall stage from [IVb] to [IVa] after receiving TPF induction chemotherapy, and two patients demonstrated a noteworthy improvement in N staging, reducing from [N2c] to [N2b]. In contrast, the fourth patient slightly improved after the induction chemotherapy and surgical resection procedures. However, the stage of the fifth patient remained unchanged before and after the treatment approach. Conclusion: The study shows that implementing TPF induction chemotherapy to surgical resection improves clinical outcomes in a subset of patients with advanced OSCC without any harmful consequences.